Sosialisasi Pentingnya Pembelajaran Public Speaking: Program Pengabdian Masyarakat di SMPN 2 Nagawutung Kecamatan Nagawutung Kabupaten Lembata - Sisilia Olivera Mambo; Baptista Varani Nahak; Stephanie Perdana Ayu Lawalu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article discusses community service program in socialization on the importance of Public Speaking for students of SMPN 2 Nagawutung, in Nagawutung District, Lembata Regency. This activity was motivated by the importance of public speaking skills in digital and globalization era, as well as the limited access to training in rural areas. The aim of this program was to increase awareness, confidence, and public speaking skills of students. Methods used were observation, lectures, simulation, evaluation, and feedback. The activity was carried out on August 2, 2024, involving students from grades 7, 8, and 9. The material provided covered the importance of public speaking, basic techniques of public speaking, and strategies for overcoming anxiety. Results showed positive responses from the village government, school officials, and students. Students showed enthusiasm and interest in the presented material. In conclusion, this program successfully increased students' awareness of the importance of public speaking skills in their academic and social lives. Recommendations include further training and development of extracurricular activities focused on public speaking to support the ongoing development of students' interests and talents.